Penerapan Hukum Terhadap Pelaku Tindak Pidana Korupsi Dalam Penyalahgunaan Dana Bantuan Operasional Sekolah - Huntoyungo, Abdul Fahri (Legalita, 2025)
Corruption is an unlawful act to enrich oneself or other people that can harm the finances of a State, at this time there have been many corruption crimes in the management of the School Operational Assistance Fund carried out by State and government officials. Corruption in the education sector is one of the most difficult forms of corruption to touch. As happened in the case of corruption in the misuse of the School Operational Assistance Fund that occurred in Batu Bara district. The issues that will be examined are how criminal liability for perpetrators of corruption crimes in the misuse of Boss Funds and how the law is applied by judges to perpetrators of corruption crimes in the abuse of Boss Funds. The writing method used is normative juridical with a case and law approach, with descriptive data analysis. That criminal liability for the perpetrators of corruption is Dana Bos as the Head of the Madrasah is responsible for the abuse of authority, opportunities, or means available to him because of his position or position. The application of the law by the Judge to the perpetrators of corruption crimes in the misuse of the Boss Fund by the Head of the Madrasah that in the facts in the trial the defendant has been legally proven guilty of committing the crime of corruption as stipulated in article 3 paragraph 1.